Dietary consumption trajectory profiles over time of French adults from the NutriNet-Santé cohort (2014–2022): multicriteria analysis of sustainability - Hafsa Toujgani; Juhui Wang; Elie Perraud; Julia Baudry; Justine Berlivet; Benjamin Allès; Hélène Fouillet; Serge Hercberg; Mathilde Touvier; Denis Lairon; Philippe Pointereau; Christian Couturier; et al. (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Dietary patterns significantly impact climate change and morbidity, making transitions to sustainable diets urgent. Few studies explore repeated dietary measures collected over several years or variations across distinct consumer profiles characterized by sociodemographic and dietary patterns. Objective Our study aims to identify dietary trajectory profiles in French adults (2014–2022), assessing environmental, nutritional, and health outcomes. Methods Consumption data from 17,187 NutriNet-Santé cohort participants (52% women, average age 48y, SD = 16) were collected via food frequency questionnaires in 2014 (weighted to the French Census), 2018, and 2022. Dietary trajectory profiles were modeled using Group-based multi-trajectory modeling based on principal component analysis of energy-adjusted consumption data. Associations with environmental (greenhouse gas (GHG) emissions) and nutritional (adherence to French dietary guidelines, diet quality index) dimensions were assessed via multivariable mixed models. Health impacts were evaluated as Disability-Adjusted Life Years (DALYs)avoided, using the Comparative Risk Assessment approach. Results Six dietary trajectory profiles (P) with distinct starting diets and evolutions were identified. P0 had average intakes, while P1 and P5 were meat-focused, with P5 showing the highest animal consumption. P3 and P4 leaned plant-based, with P4 maintaining high fish and plant intakes, and P3 increasing ruminant meat. P2 initially high in salty or sweet fatty foods, shifted significantly toward plant-based diets. Over time, GHG emissions decreased (− 5% to − 14%), diet quality (PNNS-GS2 score) improved (+ 12% to + 174%), and health risks declined in four profiles due to reduced red meat and higher whole grains/fruits but increased for P4 and P5 due to processed meat. Conclusion These profiles reflect diverse population segments with distinct dietary profiles and degrees of sustainability improvements. However, significant advancements remain limited, highlighting the need for further research on economic, psychological, and cultural factors to guide sustainable changes. Trial Registration Trial registration number: NCT03335644. URL of registration: https://clinicaltrials.gov/study/NCT03335644?id=NCT03335644&rank=1